2007
DOI: 10.1111/j.1600-6143.2006.01700.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute Pyelonephritis Represents a Risk Factor Impairing Long-Term Kidney Graft Function

Abstract: Urinary tract infections (UTIs) and acute pyelonephritis (APN) often occur after renal transplantation, but their impact on graft outcome is unclear. One hundred and seventy-seven consecutive renal transplantations were investigated to evaluate the impact of UTIs and APN on graft function. The cumulative incidence of UTIs was 75.1% and that of APN was 18.7%. UTIs occurred mainly during the first year after transplantation and Escherichia coli, Pseudomonas aeruginosa and Enteroccocus sp. were the most frequent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
222
3
28

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 269 publications
(262 citation statements)
references
References 27 publications
9
222
3
28
Order By: Relevance
“…Both UTIs and AGPN can progress and lead to bacteremia with an increased risk of morbidity and mortality, especially during the first 6-month posttransplant. This time coincides with the highest risk of acute rejection and when immunosuppressive therapy is at its maximum [1,2,[6][7][8].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Both UTIs and AGPN can progress and lead to bacteremia with an increased risk of morbidity and mortality, especially during the first 6-month posttransplant. This time coincides with the highest risk of acute rejection and when immunosuppressive therapy is at its maximum [1,2,[6][7][8].…”
Section: Discussionmentioning
confidence: 93%
“…Reports of the effect of AGPN on long-term graft and patient survival are conflicting with some showing a deleterious effect and others no difference. Pelle et al reported that AGPN was associated with poorer long-term renal graft function and Giral et al reported that the early AGPN (within the first 3 months) was significantly detrimental for graft outcome, independent of acute rejection [6,7]. Fiorante et al, however, reported no association between AGPN and long-term graft survival [8].…”
Section: Discussionmentioning
confidence: 99%
“…Important risk factors for this complication include immunosuppressive therapy, invasive urological procedures such as bladder catheterism or urethral stenting and post-transplantion urethral bladder reflux (Fig. 2) [15]. AGP should always be suspected if the patient suddenly develops fever of unknown aetiology, leucocytosis and leucocyturia as well as increased levels of C-reactive protein, even though all of them are also present in case of cystopyelitis.…”
Section: Acute Graft Pyelonephritismentioning
confidence: 99%
“…AGP should always be suspected if the patient suddenly develops fever of unknown aetiology, leucocytosis and leucocyturia as well as increased levels of C-reactive protein, even though all of them are also present in case of cystopyelitis. Differential diagnosis is fundamental, because only AGP is responsible for parenchymal damage, increasing the risk of scarring, acute rejection and worsening of renal function [15]. The use of B-mode has low sensitivity (11-40 %) and low specificity (50 %) in detecting renal parenchymal lesions in case of AGP [15,16].…”
Section: Acute Graft Pyelonephritismentioning
confidence: 99%
See 1 more Smart Citation